(untitled) (Journal for Studies in Humanities and Social Sciences, 2014)
This paper discusses the issues that are conveyed by settlement lay-out and the meaning of space at the first mission station in South Africa, Genadendal. A historical archaeology appwach was used to collect data and analyse the remains building structures, materials and settlement lay·out that have survived at Genadenda/ in an attempt to make a case for c1 "Genadendal identity" and explain the cause for its continuity. The paper argues that the study of architectural structures and settlement /ay·out from an archaeological perspective can be viewed as an exercise in studying metapho1·s since the functional aspect of architecture is a result of" conscious reactions to physical needs" at a given time as Gribble (1998) writes. Such reactions are inevitably and subtly encoded in buildings and use of space. In addition, the paper demonstratc·s that the inhabitants of Genadendai mission str.ilion developed and exhibited a "Genadendal identify" through employing unique architectural technique’ and conforming to a set of rules thot the missionories prescribed.